Recombinant expression of Thermobifida fusca E7 LPMO in Pichia pastoris and Escherichia coli and their functional characterization. (7th August 2017) - Rodrigues, Kelly B.; Macêdo, Jéssica K.A.; Teixeira, Tallyta; Barros, Jéssica S.; Araújo, Ana C.B.; Santos, Fernanda P.; Quirino, Betânia F.; Brasil, Bruno S.A.F.; Salum, Thaís F.C.; Abdelnur, Patrícia V.; Fávaro, Léia C.L.
Abstract: The discovery of lytic polysaccharides monooxygenases copper dependent (LPMOs) revolutionized the classical concept that the cleavage of cellulose is a hydrolytic process in recent years. These enzymes carry out oxidative cleavage of cellulose (and other polysaccharides), acting synergistically with cellulases and other hydrolases. In fact, LPMOs have the potential for increasing the efficiency of the lignocellulosic biomass conversion in biofuels and high value chemicals. Among a small number of microbial LPMOs that have been characterized, some LPMOs were expressed and characterized biochemically from the bacteria Thermobifida fusca, using the host Escherichia coli . In this work, the E7 LPMO protein of T. fusca was expressed both in E. coli (native DNA sequence) and Pichia pastoris (codon-optimized DNA sequence), for further analysis of oxidative cleavage, with PASC (phosphoric acid swollen cellulose) and Avicel PH-101 substrates, using mass spectrometry analysis. Mass spectra results of Avicel PH-101 and PASC cleavages by purified E7 LPMO expressed in E. coli and in P. pastoris allowed the visualization of compounds corresponding to oxidized and non-oxidized oligosaccharides. Further optimization of reactions will be performed, since it was found only one degree of polymerization (DP 7). This work demonstrated that it is possible to produce the E7 LPMO from T. fusca in the host P. pastoris, and the recombinant protein was shown to be active on cellulose. The approach used in the present work could be an alternative to produce this bacterial LPMO for cellulose cleavage. Graphical abstract: Highlights: LPMOs have potential to reducing the costs of lignocellulosic ethanol production. E7 LPMO protein expressed in P. pastoris (codon-optimized) and E. coli (native). MALDI-MS analysis allowed detection of native and oxidized cello-oligosaccharides.